TINDAK TUTUR ILOKUSI DALAM PIDATO SAMBUTAN PRESIDEN REPUBLIK INDONESIA PADA ACARA KEAGAAMAN: SEBUAH KAJIAN PRAGMATIK - Khoirunnisa, Ratna; Ardhan, Dhea Tisane; Saidatuningtyas, Ifa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Presidential speeches at religious events are often viewed as mere ceremonial formalities, yet they contain crucial pragmatic strategies for influencing public attitudes. This study examines the illocutionary speech acts in President Prabowo Subianto's welcoming speech at the 2025 National Christmas Celebration to describe their types, dominant types, and communicative functions. Using a descriptive qualitative approach with a content analysis method, the research stages include data collection from the official website of the Cabinet Secretariat and classification of speech segments based on John Searle's theory. The analysis results identified 31 occurrences of illocutionary speech acts in 25 speech segments. Quantitatively, the assertive type dominated with 12 findings (38.7%), followed by expressive with 7 findings (22.6%), directive with 5 findings (16.1%), and commissive with 4 findings (12.9%), with no declarative speech acts. The findings indicate that assertive dominance functions to frame the factual narrative of the nation's condition, while expressive strengthens interpersonal relationships with the audience. Directive speech acts are used as instruments of moral persuasion to maintain unity, while commissive speeches emphasize the government's promise of performance for the welfare of the people. The main conclusion of this study confirms that the president's speech is a strategic political discourse that utilizes a variety of linguistic strategies to construct meaning and influence in communication in the public sphere. This study demonstrates that speech choices play a vital role in shaping the image of inclusive leadership in Indonesia's multicultural society. ABSTRAK Pidato presiden dalam acara keagamaan sering kali hanya dipandang sebagai formalitas seremonial, padahal di dalamnya terkandung strategi pragmatik krusial untuk memengaruhi sikap publik. Penelitian ini mengkaji tindak tutur ilokusi dalam pidato sambutan Presiden Prabowo Subianto pada Perayaan Natal Nasional 2025 guna mendeskripsikan jenis, tipe dominan, serta fungsi komunikatifnya. Menggunakan pendekatan kualitatif deskriptif dengan metode analisis isi, tahapan penelitian meliputi pengumpulan data dari situs resmi Sekretariat Kabinet dan klasifikasi segmen pidato berdasarkan teori John Searle. Hasil analisis mengidentifikasi 31 kemunculan tindak tutur ilokusi dalam 25 segmen pidato. Secara kuantitatif, tipe asertif mendominasi dengan 12 temuan (38,7%), diikuti ekspresif 7 temuan (22,6%), direktif 5 temuan (16,1%), dan komisif 4 temuan (12,9%), tanpa adanya tindak tutur deklaratif. Temuan menunjukkan bahwa dominasi asertif berfungsi membingkai narasi faktual kondisi bangsa, sementara ekspresif memperkuat relasi interpersonal dengan audiens. Tindak tutur direktif digunakan sebagai instrumen persuasi moral untuk menjaga persatuan, sedangkan komisif menegaskan janji kinerja pemerintah bagi kesejahteraan rakyat. Simpulan utama penelitian ini menegaskan bahwa pidato presiden merupakan wacana politik strategis yang memanfaatkan keragaman strategi kebahasaan untuk membangun makna dan pengaruh komunikasi di ruang publik. Kajian ini membuktikan bahwa pilihan tuturan berperan vital dalam membentuk citra kepemimpinan yang inklusif pada masyarakat Indonesia yang multikultural.